O espaço poético em Alberto Caeiro : inter-relação com o sujeito lírico e a plasticidade da linguagem - Aguiar, Fabrício César de (2012)
This dissertation focuses on certain aspects of Alberto Caeiro's poetry, an heteronym of Fernando Pessoa, through a reading of his works The Keeper of flocks, The Amorous Shepherd and Detached Poems. It focuses on the inter-relationship man/space and, especially, the inter-relationship Caeiro/Nature, emphasizing his strong attachment to and exaltation towards Nature, reflecting his peculiar paganism. This way of relating to his own living space makes Caeiro search for "spatialization", trying to get as close as possible to the natural universe, and to do so, try to get away from the ordinary human world. Thus, he demonstrates a great aversion to the act of thinking and potentize his strengths in an attempt to feel the natural world in an intense way, considering it as sublime. Other aspects of Caeiro's poetic will also be emphasized, such as the symbolic communications created through the use of the poems chromatic and phonic substrates, his highly elaborated poetic language and the text structures used to create and transmit his poetic plasticity, such as: movement of objects, gestures or even the elements of nature, the uses of colors and the associated analogies to everyday situations, which facilitates the interaction between the text and the reader. This work will make use of some aspects of heteronymous creation in order to study in greater detail certain key aspects of Alberto Caeiro's poetry. It will emphasize the consistency between their languages and their biographical-psychological profiles, and also general peculiarities of the main heteronymous personalities: Alberto Caeiro, Ricardo Reis and Álvaro de Campos, highlighting the influences between the heteronyms and between them and Fernando Pessoa. The present study aims at contributing to the wealth of critical studies on Pessoa, taking in consideration that we did not find any work on the theme we propose.